Putting function back in dysfunction: Endothelial diseases and current therapies in hematopoietic stem cell transplantation and cellular therapies. (January 2022) - Sumransub, Nuttavut; El Jurdi, Najla; Chiraphapphaiboon, Wannasiri; Maakaron, Joseph E.
Abstract: Endothelial dysfunction is characterized by altered vascular permeability and prothrombotic, pro-inflammatory phenotypes. Endothelial dysfunction results in end-organ damage and has been associated with diverse disease pathologies. Complications observed after hematopoietic stem cell transplantation (HCT) and chimeric antigen receptor-T cell (CAR-T) therapy for hematologic and neoplastic disorders share overlapping clinical manifestations and there is increasing evidence linking these complications to endothelial dysfunction. Despite advances in supportive care and treatments, end-organ toxicity remains the leading cause of mortality. A new strategy to mitigate endothelial dysfunction could lead to improvement of clinical outcomes for patients. Statins have demonstrated pleiotropic effects of immunomodulatory and endothelial protection by various molecular mechanisms. Recent applications in immune-mediated diseases such as autoimmune disorders, chronic inflammatory conditions, and graft-versus-host disease (GVHD) have shown promising results. In this review, we cover the mechanisms underlying endothelial dysfunction in GVHD and CAR-T cell-related toxicities. We summarize the current knowledge about statins and other agents used as endothelial protectants. We propose further studies using statins for prophylaxis and prevention of end-organ damage related to extensive endothelial dysfunction in HCT and CAR-T.